Association of HIV infection with outcomes among adults hospitalized with COVID-19. (1st March 2022) - Durstenfeld, Matthew S.; Sun, Kaiwen; Ma, Yifei; Rodriguez, Fatima; Secemsky, Eric A.; Parikh, Rushi V.; Hsue, Priscilla Y.
Abstract : Objective: The aim of this study was to evaluate the association of HIV infection with outcomes among people hospitalized with COVID-19. Design: A prospectively planned analysis of the American Heart Association's COVID-19 Cardiovascular Disease Registry. Setting: One hundred and seven academic and community hospitals in the United States from March through December 2020 Participants: Consecutive sample of 21 528 adults hospitalized with COVID-19 at participating hospitals Main outcome and measure: Primary outcome was predefined as in-hospital mortality. We used hierarchical mixed effects models to assess the association of HIV with in-hospital mortality accounting for patient demographics, comorbidities, and clustering by hospital. Secondary outcomes included major adverse cardiac events (MACE), severity of illness, and length of stay (LOS). Results: The registry included 220 people with HIV (PWH). PWH were younger and more likely to be male, Non-Hispanic Black, on Medicaid, and active tobacco users. Of the study population, 36 PWH (16.4%) died compared with 3290 (15.4%) without HIV [risk ratio 1.06; 95% confidence interval (95% CI) 0.79–1.43; P  = 0.71]. After adjustment for age, sex, race, and insurance, HIV was not associated with in-hospital mortality (aOR 1.12; 95% CI 0.76–1.64; P  = 0.58) with no change in effect after adding BMI and comorbidities (aOR 1.14; 95% CI 0.78–1.68; P  = 0.51). HIV was not associated with MACE (aOR 0.99; 95% CI 0.69–1.44, P  = 0.91), COVID severity (aOR 0.96; 95% CI 0.62–1.50; P  = 0.86), or LOS (aOR 1.03; 95% CI 0.76–1.66; P  = 0.21). Conclusion: In the largest study of PWH hospitalized with COVID-19 in the United States to date, we did not find significant associations between HIV and adverse outcomes including in-hospital mortality, MACE, or severity of illness. Abstract : Supplemental Digital Content is available in the text